From Prostate Health to Hair Loss: A Comprehensive Review of Saw Palmetto’s Bioactive Compounds and Clinical Applications - Thimmannagari, Sravani; Shivaprasad, Hebbani Nagarajappa; Soni, Gaurav; Krishnamani, Madhu (Pharmacognosy Reviews)
Saw palmetto (Serenoa repens) is a palm species with rhizomatous growth, indigenous to the southeastern region of the United States. Traditionally, it has been utilized in herbal medicine for various purposes, with a notable emphasis on supporting men’s health. The berries of saw palmetto contain a range of bioactive components, including fatty acids (such as lauric, oleic, myristic, palmitic, and linoleic acids), phytosterols (β-sitosterol, campesterol, and stigmasterol), and flavonoids (rutin, isorhamnetin, quercetin, and astragalin). These constituents play a key role in the plant’s diverse biological activities, including its capacity to block 5α-reductase, the enzyme that facilitates the conversion of testosterone into Dihydrotestosterone (DHT). This inhibition is central to saw palmetto’s reported benefits in Benign Prostatic Hyperplasia (BPH) and androgenetic alopecia. Preclinical and clinical studies indicate that saw palmetto extract may help alleviate urinary symptoms related to BPH and support hair health by reducing follicle miniaturization attributed to elevated DHT. Additionally, its anti-androgenic and anti-inflammatory properties appear to add to these therapeutic effects. However, quality control challenges and variable regulatory status exist, given differences in extract standardization and oversight among countries. Overall, available research indicates that standardized extracts of saw palmetto are typically safe and well-tolerated natural option for managing conditions linked to androgen activity, such as BPH and hair loss, though attention to product quality and further research are warranted.
Keywords: 5α-reductase Inhibitor; Alopecia; Benign Prostatic Hyperplasia; Saw Palmetto; Traditional Medicine